The Future of Influencer Marketing: Trust, Authenticity, and Consumer Behavior in the Social Media Age - Nazara, Desman Serius; Nugrahaningsih, Hartanti; Abdillah, Fatimah (Jurnal Informatika Ekonomi Bisnis, 2025)
The rapid rise of influencer marketing has reshaped the landscape of consumer engagement, particularly in the social media age where trust and authenticity play critical roles in shaping purchasing behavior. This study explores how consumers perceive and respond to trust and authenticity in influencer content and how these perceptions influence decision-making processes. Utilizing a qualitative research design, in-depth semi-structured interviews were conducted with twenty active social media users to gain insights into their emotional, cognitive, and behavioral responses to influencer marketing. Thematic analysis revealed that trust is primarily built through perceived expertise, consistency, and ethical transparency, while authenticity is constructed through personal storytelling, value alignment, and selective brand endorsement. The findings also highlight the significant influence of emotional engagement and parasocial interaction in fostering consumer loyalty. Despite these positive dynamics, challenges such as commercial pressures, algorithmic content distortion, and audience skepticism threaten the sustainability of influencer credibility. The study contributes to the growing body of literature on digital consumer behavior and offers practical implications for brands and influencers striving to maintain authentic connections in an increasingly competitive digital environment.